Estimation of temperature difference between char particles and the fluidized bed in char combustion - Park, D. (1989)
In fluidized bed combustion (FBC), the understanding of various phenomena associated with char combustion is very important. The temperature difference between burning char particles and the bulk of the bed can be significant (？ 200 K), which makes analysis of char combustion more difficult. Using a simple model and a ratio of Nusselt number to Sherwood number (Nu/Sh) parameter, the effect of char size and oxygen concentration on the temperature difference can be estimated. Calculation of results using typical values for parameters show that the temperature difference can easily cover the range of measured values in the literature. At a constant value of Nu/Sh, the temperature difference increases with decrease of char size, then falls rapidly with further decrease in char size. Temperature increases with oxygen concentration and bed temperature, but decreases with the value of Nu/Sh. The transient behaviour with various oxygen concentrations was also discussed. ？ 1989.